Dealing with dysfunction : innovative problem solving in the public sector - "Jong, Jorrit de" ("Washington, D.C.", 2016)
Congressional impasse, financially untenable social programs, and fiscal crises are hallmarks of bureaucratic dysfunction today. Jorrit de Jong explains that bureaucratic dysfunction reflects a breach of contract between the government - not only as a provider of services, but also as a catalyst for improved social outcomes - and a public comprised of clients, professionals, managers, and policymakers. Dealing with Dysfunction embarks on a conceptual, theoretical, and empirical investigation to understand why bureaucratic dysfunction is a public problem and what can be done to solve it.Jorrit employs real-world data from an independent nonprofit action research team he founded: the Kafka Brigade. Building on this research, he presents 14 case studies, from licensing an Amsterdam sandwich shop to sorting out immigrant rights, which are typical of a larger problem and applicable to a broad base of clients. Utilizing data from these case studies, Dealing with Dysfunction illustrates how stakeholders can enact an inclusive process for identifying, defining, diagnosing, and remedying incidences of red tape. Further, this study highlights the failings of standard approaches to solving institutional dilemmas.Jorrit argues that effective problem solving in the public sector should adopt the following principles: Diagnostics for appropriately identifying and dissecting diverse types of dysfunctionDistribution of problem-solving capacities to connect institutions and individualsCross-organizational learning to transform accountability structuresBottom-up incrementalism that prevails over top-down regulatory reformDealing with Dysfunction offers conceptual frameworks, theoretical insights, and practical lessons for dealing with bureaucratic dysfunction in practice. It challenges conventional approaches toward "fighting bureaucracy" and "reducing red tape" and emphasizes the importance of rigorous public problem solving for making government more effective, efficient, and equitable.
Keywords: Problem solving